Research Information Dissemination through the Conversion of Thesis and Research Reports into Publishable Articles by Teaching Staff - F., Kutsanedzie; ., Achio S. (Journal of Education and Vocational Research, 2014)
Theses and research reports of academic staff in various tertiary institutions are normally deposited on shelves in university libraries year in year out. However, the essence of these rigorous academic works is tailored toward solving identified problems. A three day Workshop was held for lecturers to learn and convert their theses and research reports into publishable articles for onward submission to peer reviewed journals for subsequent review and publication. Sixty (60) lecturers registered for the workshop by submitting softcopies of their respective theses and research reports. They were conducted through the Workshop by two facilitators who presented three topics on the subject: things to consider when converting theses and research reports to publishable articles; selecting journals for article publications; and tailoring theses and research reports to the format of the selected journals. The latter topic was done with working examples to enable the participants acquire the requisite skills. The participants were made to select a peer review journal per each of their formatted articles, and allowed to follow up the steps in converting their respective copies presented. The theses and research reports that were converted to papers were submitted to editors of the respective journals selected. At the close of the Workshop about ninety (90) articles were submitted to various journals for review and subsequent publication.